Neutrality or Involvement? World War II and Evolution of Foreign Policy Concepts of the Nordic Countries - E. V. Korunova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the middle of the 20th century a unique subsystem of international relations emerged in the Northern Europe, which has turned it into one of the stablest and most peaceful regions during the Cold War period. Nowadays, rising international tensions bring new relevance to the history lessons of World War II, its origins and aftermaths. The paper examines the evolution of the Nordic countries’ views on the issue of neutrality from mid-1930s to the end of 1940s. The ﬁrst section considers the approaches of the Scandinavian countries to the establishment of a collective security system in the region in the interwar period. In that regard, the paper focuses on the Swedish project of the Northern defense alliance, which was aimed at deepening military cooperation between the states of the region and strengthening their ability to jointly deter any aggression as the best way to guarantee their neutrality. However, this project had not been implemented, because it faced both cool reactions from the leaders of Norway and Denmark and suspicion from the leading powers. According to the author, the fundamental reason for the failure of that project was that Sweden, Norway, Denmark, and Finland sought support and protection from diﬀerent, opposing great powers. The latter circumstance had also to a large extent predetermined the fate of the Scandinavian countries during the war years, when almost all of them were in one form or another involved in the conﬂict. The victory of the anti-Hitler coalition both opened new opportunities and posed new challenges for the states of the region: in the emerging bipolar world they rapidly turned into the subject matter of dispute of the superpowers. In these conditions, Sweden once again put forward the idea that in order to preserve peace in the region, the Nordic countries should be able to defend their neutrality and proposed the establishment of a Scandinavian Defense Union. In the ﬁnal section, the paper examines the reaction to this project of the Scandinavian countries, the Soviet Union, the United States, and Great Britain. The author shows that although this reaction was more than restrained, and the project was not implemented, Sweden’s initiatives contributed to the creation of a unique security architecture in Northern Europe, where each state of the region had its own role with the neutral Sweden serving as a balancing force.